What is Known About Dementia Care Recipient Violence & Aggression Against Caregivers? - Wharton, Tracy (2014)
While agitation is a known behavioral manifestation in advancing dementia, there is little in the literature about the risk to home-based caregivers, particularly in situations where severe aggression is present. This review article examines this issue with a focus on what is known and where further research is needed. Although consistent definitions failed to emerge from the literature, rates of violence by dementia care recipients against caregivers are estimated at greater than 20%, and may be the strongest predictor of nursing home placement. A review of available literature suggests that there is a need for interventions aimed at strategies to educate and protect the informal caregivers of dementia patients living at home, while advancing understanding of the communicative properties of behavior. With high rates of violence by care recipients against their caregivers, and low success rates of chemical restraints, there is substantial risk to the safety and well-being of caregivers. Several pilot interventions for nursing home settings have shown promise in reducing care recipient violence, and these may be adaptable for informal caregivers in home-based settings. Alternative delivery platforms using technology may be appropriate to consider, for real-time, flexible targeted intervention and support.